KEY LINGUISTIC TERMS AND THEIR MEANINGS (International journal of artificial intelligence, 2025)
Linguistics is the scientific study of language, encompassing various components that work together to create communication. This article provides an overview of key linguistic terms, including phoneme, morpheme, syntax, semantics, pragmatics, phonology, morphology, lexicon, discourse, sociolinguistics, and psycholinguistics. Each term is defined to help understand how language functions, from its smallest sound units to complex social interactions. These terms lay the foundation for further exploration into how language is structured, used, and processed in different contexts, both cognitively and socially.